The role of mental imagery in non-clinical paranoia - Bullock, Gemma; Newman-Taylor, Katherine; Stopa, Luisa (Journal of behavior therapy and experimental psychiatry, 2016)
Cognitive models of paranoia incorporate many of the processes implicated in the maintenance of anxiety disorders. Despite this, the role of mental imagery in paranoia remains under-researched. The current study examined the impact of a self-imagery manipulation in people with high non-clinical paranoia. We used a mixed design with one between-subjects variable (type of self-imagery) and one within-subjects variable (time – pre and post imagery manipulation). Thirty participants with high trait paranoia were allocated alternately to a positive or negative self-imagery condition. Scripts were used to elicit positive and negative self-imagery. All participants completed self-report state measures of paranoia, mood, self-esteem and self-compassion. Group by time interaction effects were found for each of the dependent variables. Positive imagery led to less state paranoia, anxiety and negative affect, and more positive affect, self-esteem and self-compassion, compared with the negative imagery group. This was a non-blind study, limited by allocation method and a brief time-frame which did not allow us to assess longevity of effects. We recruited a relatively small and predominantly female sample of people with high non-clinical paranoia. The study did not include a neutral control condition, a low paranoia comparison group, or a manipulation check following the imagery task. Self-imagery manipulations may affect paranoia, mood and self-beliefs. If the findings are replicated with clinical groups, and maintained over a longer period, this would suggest that imagery-based interventions targeting persecutory delusions might be usefully examined. [Display omitted] •We examined the impact of imagery manipulation on paranoia, mood and self-beliefs in people with non-clinical paranoia.•Positive imagery led to less paranoia and negative affect, and more positive affect, self-esteem and self-compassion.•We now need to replicate results with clinical groups, and examine longevity of effects, to determine clinical implications.